Sistemas de controle em domínios estratificados - Aquino, Paola Geovanna Patzi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work will characterize dynamical systems in the form of the so-called strati ed domain. Bressan and Hong [9] were the rst to de ne and work in strati ed domains. Roughly speaking, these are a collection of disjoint domains, each having its own dynamics; but not requiring that their domains are proximally smooth and not wedged. These terms were introduced by P. Wolenski and R. Barnard in [10]. At rst, we will establish Hamiltonian conditions to characterize weak and strong invariance for systems non-Lipschitz in strati ed domains. Secondly, we study the Hamiltonian conditions for systems weakly and strongly de- creasing and present conditions that guarantee global asymptotic stability for a strati ed dynamics and nally we present the problem Mayer type in strati ed domains where we show that the value function is the unique lower semicontinuous solution of an appropriate generalization of the classical Hamilton-Jacobi-Bellman equation for strati ed dynamics

Neste trabalho caracterizaremos sistemas dinâmicos na forma dos chamados domínios estratificados. Bressan e Hong[9] foram os primeiros a definir e trabalhar em domínios estratificados. Grosso modo, estes são uma coleção de domínios disjuntos, cada um tendo sua própria dinâmica; mas não se exige que seus domínios sejam proximamente suaves e nem wedged. Estes termos foram introduzidos por P. Wolenski e R. Barnard em[10]. Primeiramente, estabeleceremos condições Hamiltonianos para caracterizar invariância fraca e forte para sistemas não Lipschitz em domínios estratificados. Depois, estudamos condições Hamiltonianas para sistemas fracamente e fortemente decrescentes e apresentamos condições que garantem a estabilidade assintótica global para uma dinâmica estratificada e finalmente apresentamos o problema tipo Mayer em domínios estratificados em que mostramos que a função valor e a única solução semicontínua inferior de uma generalização adequada da clássica equação Hamilton-Jacobi-Bellman, para a dinâmica estratificada
Keywords: Matemática; Teoria do controle; Domínios estratificados; Estabilidade; Hamilton-Jacobi, Equações